Simulation-based inter-professional education to improve attitudes towards collaborative practice: a prospective comparative pilot study in a Chinese medical centre. Issue 11 (8th November 2017) - Yang, Ling-Yu; Yang, Ying-Ying; Huang, Chia-Chang; Liang, Jen-Feng; Lee, Fa-Yauh; Cheng, Hao-Min; Huang, Chin-Chou; Kao, Shou-Yen
Abstract : Objectives: Inter-professional education (IPE) builds inter-professional collaboration (IPC) attitude/skills of health professionals. This interventional IPE programme evaluates whether benchmarking sharing can successfully cultivate seed instructors responsible for improving their team members' IPC attitudes. Design: Prospective, pre-post comparative cross-sectional pilot study. Setting/participants: Thirty four physicians, 30 nurses and 24 pharmacists, who volunteered to be trained as seed instructors participated in 3.5-hour preparation and 3.5-hour simulation courses. Then, participants (n=88) drew lots to decide 44 presenters, half of each profession, who needed to prepare IPC benchmarking and formed Group 1. The remaining participants formed Group 2 (regular). Facilitators rated the Group 1 participants' degree of appropriate transfer and sustainable practice of the learnt IPC skills in the workplace according to successful IPC examples in their benchmarking sharing. Results: For the three professions, improvement in IPC attitude was identified by sequential increase in the post-course (second month, T2 ) and end-of-study (third month, T3 ) Interdisciplinary Education Perception Scale (IEPS) and Attitudes Towards Healthcare Teams Scale (ATHCTS) scores, compared with pre-course (first month, T1 ) scores. By IEPS and ATHCTS-based assessment, the degree of sequential improvements in IPC attitude was found to be higher among nurses and pharmacists than in physicians. In benchmarking sharing, the facilitators' agreement about the degree of participants'appropriate transfer and sustainable practice learnt 'communication and teamwork' skills in the workplace were significantly higher among pharmacists and nurses than among physicians. The post-intervention random sampling survey (sixth month, Tpost ) found that the IPC attitude of the three professions improved after on-site IPC skill promotion by new programme-trained seed instructors within teams. Conclusions: Addition of benchmark sharing to a diamond-based IPE simulation programme enhances participants' IPC attitudes, self-reflection, workplace transfer and practice of the learnt skills. Furthermore, IPC promotion within teams by newly trained seed instructors improved the IPC attitudes across all three professions.